The Influence of Profitability, Leverage, and Company Size on Earnings Management in Raw Material Companies - Putri Kezia Angelina; Florencia Irena Lawita; Agatha Violin (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2024)
The purpose of this study is to look at how profitability, debt, and business size affect earnings management in basic materials sector companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2022. This research uses a quantitative method. The population for this study is obtained from secondary data from the financial statements of enterprises in the basic materials sector from 2020 to 2022. The purposive sampling strategy was employed to choose the sample, yielding 99 data points for this investigation. The findings of this study revealed that profitability has a positive influence on earnings management, whereas firm size has a negative impact, and leverage has no effect on earnings management.